(untitled) (Comprehensive Journal of Science, 2025)
Brushless electric motors are considered the optimal and preferred choice for designing and building unmanned aerial vehicles (UAVs). This is due to the fact that these motors do not contain brushes like traditional DC electric motors, witch reduces friction and consequently increases operational efficiency and extends the motor`s lifespan. In this paper, a tool was designed to measure the performance of the brushless electric motor using a network of sensors that monitor current, voltage and rotational speed. The system also measures airspeed and send these readings to Ardunio Uno control unit, which stores and analyzes the data to determine the motor`s performance under various operating conditions. The platform includes a LCD screen to show the measured indicators in real time, as well as storage unit to save the data for future analysis. The platform was designed to be user-friendly and flexible, allowing both maintenance or and developers to utilize the data for routine maintenance or to enhance motor performance